Q&A: what are brassinosteroids and how do they act in plants? - Tang, Jiao (BMC Biol, 2016)
Brassinosteroids (BRs) are a class of polyhydroxylated steroidal phytohormones in plants with similar structures to animals’ steroid hormones. Brassinosteroids regulate a wide range of physiological processes including plant growth, development and immunity. Brassinosteroid signalling and its integration with other signalling pathways have been investigated thoroughly at the molecular level.